IMPROVING A STRONG DESTINATION IMAGE TOWARDS COMPETITIVE ADVANTAGE IN DESTINATION HALAL TOURISM TO THE SUMENEP PALACE MUSEUM - Fauzi, Moh.; Syarif, Muh. (JURNAL EKBIS, 2025)
The tourism sector has grown significantly and plays an important role in today's international competition. In recent years, many Muslim travelers from various countries have enjoyed traveling, which has led to the emergence of the concept of halal tourism destinations to attract Muslim visitors to this tourism sector. Of course, Indonesia must be able to develop competitive advantages, especially in the halal tourism sector. One of the famous halal tourist destinations is the Sumenep Palace Museum. In order for this tourism to be more widely known, it is necessary to develop tourism which can be done by strengthening the competitive advantage of tourism through Branding, Storytelling, and Engagement. Therefore, this study was conducted with the aim of determining whether Branding, Storytelling, and Engagement affect the competitive advantage of the Sumenep Palace Museum halal tourist destination. This study uses a quantitative method and obtains the results that Branding, Storytelling, and Engagement affect the competitive advantage of the Sumenep Palace Museum both partially and simultaneously..